Sistem Informasi Manajemen Toko Berbasis Web dengan Menggunakan Barcode Scanner untuk Entri Data - Yudantoro, Tri Raharjo; Suyanto, Budi; Chasanah, Annisa Uswatun (JTET (Jurnal Teknik Elektro Terapan), 2017)
Management information system is essential for an entrepreneur, because the management information system is indispensable to know the management of the business quickly and accurately. Faiza Collection store is a retail and wholesale stores that do not have a store management information system. Faiza Collection store sells uniforms and clothing in Tanjung Pinang, Riau Islands which management data is still manual. The objective of this final project is to make store management information system to facilitate the performance of the store Faiza Collection. Store management information system was created using the Waterfall method, where each step in the methodology of research carried out in sequence, starting from the stage of requirements analysis, system design, writing code, testing programs, as well as the implementation and maintenance program. In the construction of this store management information system using CodeIgniter framework, php, javascript and html. The stores management information system has been successfully tested with both the 3 browser, the Mozilla Firefox, Google Chrome, and Internet Explorer. Based on test results obtained using a questionnaire method level of user satisfaction Store Management Information System Web-based with Barcode Scanner for data entry of 87.05%, which means that users are very satisfied with the functions and features of this system.Keywords: barcode scanners, CodeIgniter framework,Â information systems, store management, web